Bifunctional Conducting Polymer Coated CoP Core–Shell Nanowires on Carbon Paper as a Free‐Standing Anode for Sodium Ion Batteries. Issue 20 (6th April 2018) - Zhang, Jing; Zhang, Kai; Yang, Junghoon; Lee, Gi‐Hyeok; Shin, Jeongyim; Wing‐hei Lau, Vincent; Kang, Yong‐Mook
Abstract: This study proposes a conformal surface coating of conducting polymer for protecting 1D nanostructured electrode material, thereby enabling a free‐standing electrode without binder for sodium ion batteries. Here, polypyrrole (PPy), which is one of the representative conducting polymers, encapsulated cobalt phosphide (CoP) nanowires (NWs) grown on carbon paper (CP), finally realizes 1D core–shell CoP@PPy NWs/CP. The CoP core is connected to the PPy shell via strong chemical bonding, which can maintain a Co–PPy framework during charge/discharge. It also possesses bifunctional features that enhances the charge transfer and buffers the volume expansion. Consequently, 1D core–shell CoP@PPy NWs/CP demonstrates superb electrochemical performance, delivering a high areal capacity of 0.521 mA h cm −2 at 0.15 mA cm −2 after 100 cycles, and 0.443 mA h cm −2 at 1.5 mA cm −2 even after 1000 cycles. Even at a high current density of 3 mA cm −2, a significant areal discharge capacity reaching 0.285 mA h cm −2 is still maintained. The outstanding performance of the CoP@PPy NWs/CP free‐standing anode provides not only a novel insight into the modulated volume expansion of anode materials but also one of the most effective strategies for binder‐free and free‐standing electrodes with decent mechanical endurance for future secondary batteries. Abstract : Bifunctional polypyrrole (PPy)‐coated CoP nanowires/carbon paper exhibit strong chemical interaction between CoP and PPy, which induces the formation of a Co–PPy framework during charge/discharge. The electronic conductivity and structural stability are effectively improved by the Co‐PPy framework, resulting in high cyclic stability and rate capability compared with the uncoated sample.